2017
DOI: 10.1186/s13046-017-0491-7
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant activation of hedgehog signaling promotes cell proliferation via the transcriptional activation of forkhead Box M1 in colorectal cancer cells

Abstract: BackgroundRecent evidence suggests that the aberrant activation of Hedgehog (Hh) signaling by Gli transcription factors is characteristic of a variety of aggressive human carcinomas, including colorectal cancer (CRC). Forkhead box M1 (FoxM1) controls the expression of a number of cell cycle regulatory proteins, and FoxM1 expression is elevated in a broad range of human malignancies, which suggests that it plays a crucial role in tumorigenesis. However, the mechanisms underlying FoxM1 expression are not fully u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…FoxM1 is a member of the Forkhead box (Fox) transcription factor family, which has been shown to be over-expressed in various cancers and studies have shown that alterations in FoxM1 signaling were associated with carcinogenesis. FoxM1 is substantially elevated in several aggressive human carcinomas and can contribute to oncogenesis in many tissue types, including breast [ 12 ], hepatocellular [ 13 ], prostate [ 14 ], lung [ 15 ], and colorectal cancers [ 16 ]. Aberrant FoxM1expression was found to be a common molecular alteration in malignant glioma [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…FoxM1 is a member of the Forkhead box (Fox) transcription factor family, which has been shown to be over-expressed in various cancers and studies have shown that alterations in FoxM1 signaling were associated with carcinogenesis. FoxM1 is substantially elevated in several aggressive human carcinomas and can contribute to oncogenesis in many tissue types, including breast [ 12 ], hepatocellular [ 13 ], prostate [ 14 ], lung [ 15 ], and colorectal cancers [ 16 ]. Aberrant FoxM1expression was found to be a common molecular alteration in malignant glioma [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 75% of these binding sites act as cis-activation elements, but they do not all function through the same basic mechanisms. For example, glioma-associated oncogene homolog 1 (Gli1), CCCTC-binding factor (CTCF), cAMP responsive element-binding protein (CREB), signal transducer and activator of transcription 3 (STAT3), and E2F interact directly with their binding sites and upregulate FOXM1 expression [ 9 , 30 – 34 ]. In human colorectal cancer (CRC), Gli1 regulates FOXM1 by directly binding to its promoter at BS4 (GCCCACCCA), which contributes to the proliferation of CRC cells [ 9 ].…”
Section: Transcriptional Regulation Of Foxm1mentioning
confidence: 99%
“…For example, glioma-associated oncogene homolog 1 (Gli1), CCCTC-binding factor (CTCF), cAMP responsive element-binding protein (CREB), signal transducer and activator of transcription 3 (STAT3), and E2F interact directly with their binding sites and upregulate FOXM1 expression [ 9 , 30 – 34 ]. In human colorectal cancer (CRC), Gli1 regulates FOXM1 by directly binding to its promoter at BS4 (GCCCACCCA), which contributes to the proliferation of CRC cells [ 9 ]. The DNA-binding protein, CTCF, may regulate the motility and invasiveness of primary hepatocellular carcinoma (HCC) cells via interaction with the CTCF-binding site(s) located in the proximal promoter of FOXM1 [ 30 ].…”
Section: Transcriptional Regulation Of Foxm1mentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrantly active Hh signaling promoted proliferation of CRC cells by directly binding to the promoter of FoxM1 and increasing its transactivational activity [93]. FoxM1 inhibition dramatically reduced colony formation and growth rate of HCT116 cells [93]. Three-dimensional organoid culture models were prepared from tissues of colorectal cancer patients.…”
Section: Shh/gli Signaling In Colorectal Cancer Cancer Promoting Rolementioning
confidence: 99%